Pengaruh pemberian seduhan kering bunga rosella terhadap penurunan tekanan darah - Gilang, Muhammad (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Hypertension is the condition of blood pressure above normal when measurement pressure systolic larger than 140 mmhg and or diastolik larger than 90 mmhg. Hypertension with stroke and heart disease are number one cause of death in Indonesia. The hypertension mechanism in the body controlled by baroreceptors, regulation of body fluid’s volume, rennin-angiotension system and autoregulation. The handling of hypertension need to control blood pressure and prevent complication that could happen because hypertension. The theraphy of hypertension could be done by pharmacology and non-pharmacology. Pharmacology theraphy can be use drugs like diuretic anti-hypertension, beta-blockers, ace inhibitors, and ca blockers. Non-pharmacology theraphy using the lifestyle and consumption of natural ingredients to reduce the blood pressure. Either plant considered helpful to reduce the blood pressure is rosella’s flower. Rosella’s flower (Hibiscus Sabdariffa) is a plant that many known and used in various country including Indonesia. Part of these plant can be use is the red one. The influence of rosella’s flower in reductions the blood pressure because the compound are gassypetin, antosianin, and glucoside hibiscin. They are believed to substances as diuretics because can reduce viscosity of blood and blood pressure. Lot of research shows the influence of the provision of rosella’s extract to decrease blood pressure and having the effect of proportional to the ordinary anti-hypertension by administering a sedative. Through this, rosella’s flower can be the one alternative therapy for hypertension’s patients. And the conclusion is rosella’s flower extract having influence to reduce the blood pressure.